Electroencephalogram effects of armodafinil: Comparison with behavioral alertness. (1st August 2013) - Conrado, Daniela J.; Bewernitz, Michael; Ding, Mingzhou; Cibula, Jean; Seubert, Christoph; Sy, Sherwin K. B.; Eisenschenk, Stephan; Derendorf, Hartmut
Abstract Development of central nervous system‐acting drugs would be enhanced by suitable biomarkers that reflect the targeted pathophysiologic brain state. The electroencephalogram (EEG) has several characteristics of an ideal biomarker and can be promptly adapted to pre‐clinical and clinical testing. The aim of this study was to evaluate EEG as a measure of the wakefulness‐promoting effect of armodafinil in sleep deprived healthy subjects. Armodafinil pharmacodynamics were simultaneously assessed by EEG‐ and behavioral‐based measures including a well‐established measure of alertness. Using two quantitative EEG‐based measures—power spectral and event‐related brain activity analyses—we observed that armodafinil mitigated the slowing of brain activity and the decrease of the event‐related brain activity caused by sleep deprivation. Armodafinil‐induced changes in EEG are in agreement and explain up to 73.1% of the armodafinil‐induced changes in alertness. Our findings suggest that EEG can serve as a marker of the wakefulness‐promoting drug effect.